THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND VOLUNTARY DISCLOSURE ON INFORMATION ASYMMETRY - Faishal Adani Farras; Faisal Faisal (Diponegoro Journal of Accounting, 2020)
Financial statement is very important as a source of financial information of a company to internal and external stakeholder. However, information in the company is not shared fairly to external parties. The situation where internal parties in the company received more information than external parties is called information asymmetry. The implementation of good corporate governance and voluntary disclosure hypothetically influence the information asymmetry based on some previous research.Thus, this study aims to examine how the implementation of good corporates governances and voluntary disclosure effecting the information asymmetry. This study will be using 87 companies as the sample from 2016-2018. The companies used in this study consist of trading, investment and services company from Indonesian Stock Exchange. The result of this study shows that good corporate governance and voluntary disclosure are positively effects the information asymmetry.